Problemes politiques, financiers et technologiques lies au developpement de l'elevage en Afrique subsaharienne: Quelques questions cruciales - Anteneh, A.; Anteneh, B. (1988)
Examines the role and importance of the livestock subsector of Africas' agricultural sector, its performance over the last two decades, the constraints which limit its development and the progress being made in solving theese constraints.